MALAYSIAN PARENTS’ FEEDBACK ON THREE PROXY-RATED ASSESSMENTS USED IN PEDIATRIC REHABILITATION - Farahiyah Wan Yunus; Michelle Bissett; Stefania Penkala; Masne Kadar; Karen Liu (Malaysian Journal of Public Health Medicine, 2018)
Assessing a child’s functional abilities and limitations can provide useful information for occupational therapists to develop individualised intervention plans. Usually paediatric assessments require parents to rate their child on different domains of health and functional performance. To do so, parents need to be able to understand the assessment content and instructions to rate their child accurately. The primary purpose of this study was to examine if parents in Malaysia understood the content and instructions of three assessments: the Sensory Profile Caregiver Questionnaire (SP), the Sensory Processing Measure Home Form (SPM) and the Behaviour Rating Inventory of Executive Function Parent Form (BRIEF). The secondary purpose was to examine perceptions about the clarity and relevancy of each of the items in each assessment. Thirty parents, recruited using convenience sampling, completed a survey about the assessments. In general, the parents indicated no problems or only minor problems in understanding the content and instructions of all three assessments. The parents also provided comments to improve the clarity of the assessment items. Comments were primarily related to the terms or jargon language used. Elaborations of the terms or jargon were later provided based on the parents’ comments. All three assessments were identified as relevant to be used in the Malaysian population. The results suggest that all three assessments can be used by parents and are suitable to be implemented by occupational therapists working with children in Malaysia.